Modulating inflammation through the negative regulation of NF‐κB signaling. Issue 6 (1st February 2018) - Rothschild, Daniel E.; McDaniel, Dylan K.; Ringel‐Scaia, Veronica M.; Allen, Irving C.
Abstract: Immune system activation is essential to thwart the invasion of pathogens and respond appropriately to tissue damage. However, uncontrolled inflammation can result in extensive collateral damage underlying a diverse range of auto‐inflammatory, hyper‐inflammatory, and neoplastic diseases. The NF‐κB signaling pathway lies at the heart of the immune system and functions as a master regulator of gene transcription. Thus, this signaling cascade is heavily targeted by mechanisms designed to attenuate overzealous inflammation and promote resolution. Mechanisms associated with the negative regulation of NF‐κB signaling are currently under intense investigation and have yet to be fully elucidated. Here, we provide an overview of mechanisms that negatively regulate NF‐κB signaling through either attenuation of signal transduction, inhibition of posttranscriptional signaling, or interference with posttranslational modifications of key pathway components. While the regulators discussed for each group are far from comprehensive, they exemplify common mechanistic approaches that inhibit this critical biochemical signaling cascade. Despite their diversity, a commonality among these regulators is their selection of specific targets at key inflection points in the pathway, such as TNF‐receptor‐associated factor family members or essential kinases. A better understanding of these negative regulatory mechanisms will be essential to gain greater insight related to the maintenance of immune system homeostasis and inflammation resolution. These processes are vital elements of disease pathology and have important implications for targeted therapeutic strategies. Abstract : Review of regulators that negatively modulate NF‐ÎºB signaling to attenuate inflammation and promote resolution.